ARCHITECTURE OF MONITOR API TO HANDLE INTEGRATION DATA PROBLEM IN DATABASE-MICROSERVICE - Esa Fauzi; Yani Iriani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Microservice is one of the architectural trends in software development. Microservices divide normally large applications into smaller, more independent parts. One of these small parts can be a function that communicates with the database (database-per-service). However, in microservice architecture, sometimes not only one database is used. In one transaction of the microservice architecture sometimes requires inputting into multiple databases. This can be a problem if in one of the input processes there is an error in one of the services, causing loss of data integration between databases. Based on this problem we proposed a system to monitor the transaction process. The monitor that we have developed will check the data that is entered into the database at each microservice service. If there is an error, the monitor will roll back the failed transaction.